2005
DOI: 10.1097/01.aids.0000180794.27896.fb
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine use is associated with increased HIV incidence among men who have sex with men in San Francisco

Abstract: We examined the association between amphetamine use and HIV incidence for 2991 men who have sex with men (MSM) who tested anonymously for HIV in San Francisco. HIV incidence among 290 amphetamine users was 6.3% per year (95% CI 1.9-10.6%), compared with 2.1% per year (95% CI 1.3-2.9%) among 2701 non-users (RR 3.0, 95% CI 1.4-6.5). HIV prevention programmes in San Francisco should include efforts to reduce amphetamine use and associated high-risk sexual behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(115 citation statements)
references
References 7 publications
7
105
2
Order By: Relevance
“…Numerous studies document MA use by men who have sex with men to enhance sexual activity, especially at "circuit parties" involving multiple partners, contributes to unsafe sex behaviors that increase the risk of HIV transmission, leads to noncompliance with prescription medication to treat HIV, and interferes with antiretroviral therapy. [9][10][11][12][13][14]16 Because of the serious health risk associated with MA, identifying and entering users into substance abuse treatment is critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies document MA use by men who have sex with men to enhance sexual activity, especially at "circuit parties" involving multiple partners, contributes to unsafe sex behaviors that increase the risk of HIV transmission, leads to noncompliance with prescription medication to treat HIV, and interferes with antiretroviral therapy. [9][10][11][12][13][14]16 Because of the serious health risk associated with MA, identifying and entering users into substance abuse treatment is critical.…”
Section: Discussionmentioning
confidence: 99%
“…2,[5][6][7] Methamphetamine is rapidly surpassing other illicit drugs in popularity throughout the United States, particularly among homosexual men, and is considered to be in epidemic proportions in the western and midwestern states. 2,[8][9][10][11][12][13][14] Dentists successful treatment and prevention of disease progression. The purpose of this paper is to alert health care providers to the dental signs and symptoms of MA abuse.…”
Section: Introduction Rmentioning
confidence: 99%
“…Injection practices (CDC, 2003) and risky sexual behaviors (Leigh & Stall, 1993) among illicit drug abusing populations have greatly contributed to the rapid growth and spread of HIV in the U.S. Much attention regarding high rates of HIV among illicit drug users in the U.S. has centered on heroin and cocaine/crack users (Gyarmathy, Neaigus, Miller, Friedman, & Des Jarlais, 2002;Neaigus, Miller, Friedman, & Des Jarlais, 2001). However, a growing number of studies have identified methamphetamine (MA) use as a significant cofactor associated with increased HIV infection (Schwarcz, Scheer, McFarland, Katz, Valleroy, et al, 2007;Colfax, Mansergh, Guzman, Vittinghoff, Marks, et al, 2001;Colfax, Vittinghoff, Husnik, McKirnan, Buchbinder, et al, 2004;Colfax, Coates, Husnik, Huang, Buchbinder, et al, 2005;Buchacz, McFarland, Kellogg, Loeb, Holmberg, et al, 2005). Most of this work to date has been on men who have sex with men (MSM) populations (Peck, Shoptaw, Rotheram-Fuller, Reback, & Bierman, 2005;Halkitis, Parsons, & Stirratt, 2001;Reback, Larkins, & Shoptaw, 2004) ;Frosch, Shoptaw, Huber, Rawson, & Ling, 1996;Gorman, Morgan, & Lambert, 1995;Paul, Stall, & Davis, 1993;Shoptaw, Reback, Frosch, & Rawson, 1998;Semple, Patterson, & Grant, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In several studies of gay men, illicit drug use in general has been found to be associated with unprotected anal intercourse with casual partners -UAIC Strathdee et al, 1998;Woody et al, 1999;Rusch et al, 2004), and, in some studies (Darrow et al, 2005;Bolding et al, 2006), this was particularly true of amphetamine type stimulants. In some instances, illicit drug use in general has also been associated with HIV seroconversion DiFranceisco et al, 1996) as has the use of amphetamine type stimulants in particular (Buchacz et al, 2005;Boddiger, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which illicit drug use influences sexual risk behaviour among gay men remains a key question, and one that has been the subject of considerable debate (Clatts et al, 2005;Halkitis et al, 2001;Colfax et al, 2001;Worth and Rawstorne, 2005;Smith et al, 2004;Slavin, 2004;Buchacz et al, 2005;Boddiger, 2005). The research has been beset by problems in consistency of terminology, differences in the drugs examined, poor adjustment for confounding variables, and a reliance on cross-sectional research (Drumright, Patterson et al 2006).…”
Section: Introductionmentioning
confidence: 99%